Similarity of subjective symptoms between autism spectrum disorder and attention‐deficit/hyperactivity disorder in adults: Preliminary findings - Akari Nakagawa; Wakaho Hayashi; Takashi Nishio; Yoichi Hanawa; Keisuke Aoyagi; Yuka Okajima; Akira Iwanami (Wiley, 2021)
Abstract Aim The purpose of this study was to examine the symptoms of autism spectrum disorder (ASD) and attention‐deficit/hyperactivity disorder (ADHD) in the adult clinical population using the Autism‐Spectrum Quotient (AQ) and the Adult ADHD Rating Scales self‐report screening version (CAARS‐S:SV). Methods We included 50 adults with ASD and 52 with ADHD diagnosed using the DSM‐5 criteria. Clinical symptoms were evaluated using the AQ and CAARS‐S:SV. Results The AQ score was elevated in the ADHD group and the CAARS scores were increased in the ASD group. Specifically, the total AQ score in adults with ADHD was lower than that in the ASD group, but was higher than that in controls. Similarly, the CAARS scores in adults with ASD were lower than in those with ADHD, but were higher than those in controls. No significant correlations were found between AQ, CAARS Inattention/Memory Problems, and CAARS Hyperactivity/Restlessness scores in both the ASD and ADHD groups. Conclusion While adults with ASD and ADHD exhibited similar clinical symptoms, the absence of AQ‐CAARS correlations suggests the need for examining factors other than the apparent similarity of clinical symptoms of the two disorders.